An investigation of the relationship between Chinese college EFL students' language learning motivation and language learning strategies - Yang, Wenwen (Animo Repository, 2012)
English, as a foreign language, has been widely learned throughout China in the past thirty years. Second/foreign language proficiency has been consistently linked with some individual learner differences. Language learning motivation and strategies are considered to be two major variables to bring about differences in individual learners (Ellis, 1985). The present study, using a modified version of Gardner’ (1985) framework AMTB and Oxford’s (1990) framework SILL, aims to investigate language learning motivation and strategies as well as the relationship between their language learning motivation and strategy employment of 216 Chinese EFL college students, who are classified by language proficiency, major and gender. The results reveal that there is a significant correlation between language learning motivation and language learning strategy use. Meanwhile, the paper provides implications for current instructional practices to help Chinese English teachers gain a detailed understanding of motivation held and strategy employed by their students and therefore narrow the gap between learning and instruction. Keywords: Language learning motivation, language learning strategy, relationship